The Roles of Apoptosis in Swine Response to Viral Infection and Pathogenesis of Swine Enteropathogenic Coronaviruses - Xu, Zhichao; Zhang, Yun; Cao, Yongchang (Frontiers in Veterinary Science, 2020)
Apoptosis is a tightly regulated mechanism of cell death that plays important roles in various biological processes including biological evolution, multiple system development, anticancer and viral infections. Swine enteropathogenic coronaviruses invade and damage villous epithelial cells of the small intestine causing severe diarrhea with high mortality rate in suckling piglets. Transmissible gastroenteritis virus (TGEV), Porcine epidemic diarrhea virus (PEDV), Porcine deltacoronavirus (PDCoV) and Porcine enteric alphacoronavirus (PEAV) are on the top list of commonly-seen swine coronaviruses with a feature of diarrhea, resulting in significant economic losses to the swine industry worldwide. Apoptosis have been shown to be involved in the pathogenesis process of animal virus infectious diseases. Understanding the roles of apoptosis in host responses against swine enteropathogenic coronaviruses infection contribute to disease prevention and control. Here we summarize the recent findings that focus on the apoptosis during swine coronaviruses infection, in particular, TGEV, PEDV, PDCoV and PEAV.